Effect of batch initial velocity on the glass furnace efficiency - Soleimanian, Nasim; Jolly, Mark R.; Dearn, Karl; Brinkman, Oliver; Brinkman, William (Wiley, 2014)
Glass manufacturing is a heat intensive process. There is a direct coloration between the batch distribution techniques and the furnace energy consumption, productivity, and quality of the glass manufactured. All four major segments (float, container, fibre, and specialty glasses) would benefit from using an optimised batch distribution technique where possible. Oscillating batch chargers (OBC) have been in use since the early 70s, despite their superior batch shape, coverage, and in turn positive effects on the energy consumption (Soleimanian, TMS 2013) and productivity of the furnace they are almost exclusively used in container glass manufacturing. The OBC’s main difference compared with other charging methods is its ability to directly influence the batch initial velocity. This paper reports on results achieved in two CFD models (in Flow 3D and GFM) used to study effect of the machine on the overall energy consumption in the doghouse and the melt space.